The Role of Platelet-Rich Plasma Injections in the Treatment of Ovarian Insufficiency - حسن ميس; أحمد عبد الرحمن; لينا رمضان (Tishreen University Journal -Medical Sciences Series, 2024)
The research aimed to evaluate the effectiveness of platelet-rich plasma injections in treating ovarian insufficiency in terms of FSH values, and to study the effect of age on the improvement of FSH values for patients before and after the injection. (13) female patients of reproductive age were admitted to the women’s clinic at Tishreen University Hospital, who were suffering from infertility due to ovarian insufficiency. The necessary general and hormonal analyzes were performed, ultrasound imaging of the uterus and appendages was performed to diagnose ovarian insufficiency, and a semen analysis of the husband was performed (provided that it was normal). The patient was prepared for laparoscopy in order to inject platelet-rich plasma after the end of the menstrual cycle in the first phase of the cycle (10) ml of platelet-rich plasma was prepared from the blood of the concerned patient. The results of the research showed that platelet-rich plasma injections are a promising treatment for ovarian insufficiency, as this treatment can help improve fertility and women’s general health. This is indicated by the fact that (69.23%) of the female patients in the sample experienced an improvement in ovulation after the injection procedure. The significance of FSH values after injection indicates its return to normal values compared to its values before injection, which indicate that it has risen above normal limits.